Impairment of Phosphatidylinositol Metabolism in a Patient with a Bleeding Disorder Associated with Defects of Initial Platelet Responses - Lages, Bruce; Weiss, Harvey J (Thrombosis and Haemostasis, 1988)
Phosphoinositide/polyphosphoinositide (PI/PPI) metabolism, measured by the increase of 3H-phosphatidic acid (PA) and the decrease of 3H-phosphatidylinositol (PI) in 3H-arachidonate- labeled platelet suspensions, was assessed in five patients whose platelet functional defects included impaired initial rates of ADP, epinephrine and U44069 aggregation in platelet-rich plasma (PRP). In one patient, 3H-PA formation induced by collagen and thrombin was reduced or absent on two of three occasions, and the decrease in 3H-PI was reduced on one of these two occasions in response to collagen and A23187, and on all 3 occasions in response to thrombin. The variations in the formation of 3H-PA in this patient on different occasions broadly paralleled the variations in the initial rates of ADP and U44069 aggregation and in epinephrine aggregation seen in PRP. No such abnormalities of PI metabolism were found in four other patients with similar, but not identical, functional defects. These results suggest an impairment affecting metabolism of PI/PPI via the PI/PPI cycle in this patient's platelets. The association of abnormalities of PI metabolism with defects of initial platelet responses provides further support for a physiological role of phosphoinositide metabolism in the early activation mechanisms of platelets.
Keywords: Platelets; Phosphoinositides; Phosphatidic acid; Blood platelet disorders